2005
DOI: 10.1155/2005/248714
|View full text |Cite
|
Sign up to set email alerts
|

Total and Specific Immunoglobulin E and Their Relationship to Respiratory Symptoms in Quebec Children and Adolescents

Abstract: Allergic sensitization is a major determinant in the development of asthma, wheezing and rhinitis in children and adolescents in the province of Québec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…Factors that can affect IgE levels, including the environment, location, age, and sex, did not affect our results. The number and type of allergens in symptomatic patients were not found to affect tIgE levels in this study as opposed to other reports …”
Section: Discussioncontrasting
confidence: 99%
“…Factors that can affect IgE levels, including the environment, location, age, and sex, did not affect our results. The number and type of allergens in symptomatic patients were not found to affect tIgE levels in this study as opposed to other reports …”
Section: Discussioncontrasting
confidence: 99%
“…Our cohort analyses highlighted significant associations between sensitization to pet and pollen allergens and asthma morbidity, which is in line with several previous studies (Lévesque et al, 2005; Simpson et al, 2005; Simpson et al, 2015). The novelty of our study is that many of these associations remain within twin pairs, although with wider confidence intervals for both MZ and DZ pairs.…”
Section: Discussionsupporting
confidence: 92%
“…Simpson et al (2015), who in their study on 11-year-old children tested allergen components grouped into categories, found the category including all domestic pet allergens to be most strongly associated with asthma morbidity. Lévesque et al (2005) found significant differences in sensitization to cat in children with and without asthma, whereas none were observed for dog and timothy sensitization. In accordance with Ghunaim et al (2006), we noted higher estimates for the associations for birch pollen and asthma than for timothy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sensitization to indoor allergens is an important risk factor for allergic asthma (1–6). Besides house dust mite and cockroach, domestic cat is one of the most significant sources of indoor allergens world‐wide.…”
mentioning
confidence: 99%